ANALISIS PERTUMBUHAN EKONOMI MASYARAKAT DI KABUPATEN SIAK DALAM PERSFEKTIF KERUANGAN TAHUN 2007-2016 - yulia lestari; Sri Mariya (JURUSAN GEOGRAFI FIS UNP, 2019)
ABSTRACT The purpose this research to analyze the economic growth of the people in Siak Regency from 2007-2016 by linking economic growth in the spatial perspective in Siak Regency. This type of research uses descriptive quantitative methods. The results of research show that the economic growth of the people in Siak Regency in 2007-2016 each year experienced an increase and a decrease, in 2009 to 2010 economic growth had increased by 764.36% which was categorized as fast. Based on the analysis of the Siak Regency Locations Qoutient (LQ) in 14 sub-districts of the agricultural sector GRDP, it includes the plantation subsector and the food subsector. The LQ results which are the base sector of the plantation subsector are oil palm plants and for the food subsector which is the base sector, cassava plants. So that from the analysis of the results of the LQ it can be seen the type of land use, where in 2007 the use of land for plantations was 630,999 ha and in 2016 it was 788,373 ha. As for the rice fields in 2007 to 2016 the land use turned into plantations. Keywords: Economic Growth, GDP , Base and Non-Base Sectors